KESADARAN HUKUM SEBAGAI PERWUJUDAN NEGARA DEMOKRASI - Fransiska Novita Eleanora (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2012)
Sense of justice is awareness of the every man whereof the law or does ought to punish that, a certain category from psychological life of we are by which we differentiate between laws and doesn't punish, between properly are done and not properly is done. Effective action or way to increase public sense of justice is in the form of drastic a keepment for example memperberat law threat or with interest tightens settlement of adherence of citizen to code/law. Research Method is bibliography study, the result in forming of sense justice democratic country plays a part to form an state order is cleanness, and orders made by power can be implemented by public, without existence of element of constraint from others, and sense of justice is materialization a state, what can bring the citizen toward democratic country.